Caught in the middle: China and India in Sudan's transition - Daniel Large; Luke Patey (Danish Institute for International Studies (DIIS), 2010)
Sudan is at an important, historic moment. The upcoming referendum vote may very likely result in the South becoming an independent state. Since the landmark signing of the Comprehensive Peace Agreement in 2005, China, and to a lesser extent India, have become even more important political and economic partners of the ruling National Congress Party in Khartoum. Generally, commentaries and studies covering China and India's relations with Sudan focus on their interactions with the central government in Khartoum. However, this paper finds that both have also followed a necessary hedging strategy by establishing quasi-diplomatic relations with the Sudan People's Liberation Movement-run Government of Southern Sudan in Juba. Both have expanded economic and political relations beyond investment in Sudan's oil sector and beyond merely engaging Khartoum. Chinese and Indian engagement with the GOSS in Juba marks a major shift in policy from dealing exclusively with the central government. The adaptation of both to political developments, however, does not leave them invulnerable to present uncertainties revolving around Sudan's potential split. Due to its economic role in Sudan, China in particular is in a unique position to promote a peaceful transition.
Keywords: 330